Outcomes of Cryoballoon Ablation in High- and Low-Volume Atrial Fibrillation Ablation Centres: A Russian Pilot Survey. (12th November 2015) - Mikhaylov, Evgeny N.; Lebedev, Dmitry S.; Pokushalov, Evgeny A.; Davtyan, Karapet V.; Ivanitskii, Eduard A.; Nechepurenko, Anatoly A.; Kosonogov, Alexey Ya.; Kolunin, Grigory V.; Morozov, Igor A.; Termosesov, Sergey A.; Maykov, Evgeny B.; Khomutinin, Dmitry N.; et al.
Abstract : Purpose . The results of cryoballoon ablation (CBA) procedure have been mainly derived from studies conducted in experienced atrial fibrillation (AF) ablation centres. Here, we report on CBA efficacy and complications resulting from real practice of this procedure at both high- and low-volume centres. Methods . Among 62 Russian centres performing AF ablation, 15 (24%) used CBA technology for pulmonary vein isolation. The centres were asked to provide a detailed description of all CBA procedures performed and complications, if encountered. Results . Thirteen sites completed interviews on all CBAs in their centres (>95% of CBAs in Russia). Six sites were high-volume AF ablation (>100 AF cases/year) centres, and 7 were low-volume AF ablation. There was no statistical difference in arrhythmia-free rates between high- and low-volume centres (64.6 versus 60.8% at 6 months). Major complications developed in 1.5% of patients and were equally distributed between high- and low-volume centres. Minor procedure-related events were encountered in 8% of patients and were more prevalent in high-volume centres. Total event and vascular access site event rates were higher in women than in men. Conclusions . CBA has an acceptable efficacy profile in real practice. In less experienced AF ablation centres, the major complication rate is equal to that in high-volume centres.